Advances in Nanoparticulate Drug Delivery Approaches for Sublingual and Buccal Administration - Hua, Susan (Frontiers in Pharmacology, 2019)
The sublingual and buccal routes of administration have significant advantages for systemic drug delivery. They have shown to be an effective alternative to the traditional oral route, especially when fast onset of action is required. Drugs can be rapidly and directly absorbed into the systemic circulation via venous drainage to the superior vena cava. Therefore, they are useful for drugs that undergo high hepatic clearance or degradation in the gastrointestinal tract, and for patients that have swallowing difficulties. Drugs administered via the sublingual and buccal routes are traditionally formulated as solid dosage forms (e.g. tablets, wafers, films, patches), liquid dosage forms (e.g. sprays and drops), and semi-solid dosage forms (e.g. gels). Conventional dosage forms are commonly affected by physiological factors, which can reduce the contact of the formulation with the mucosa and lead to unpredictable drug absorption. There have been a number of advances in formulation development to improve the retention and absorption of drugs in the buccal and sublingual regions. This review will address the physiological and pharmaceutical considerations influencing sublingual and buccal drug delivery, as well as the conventional and novel drug delivery approaches.